Cars! cars! cars! - Maccarone, Grace; Carter, David A. (New York : Scholastic, 1995)
Simple rhymes and pictures portray many different kinds of cars.
"Cartwheel books."
Keywords: Automobiles -- Fiction; Stories in rhyme